(3GdJHUQI aj GdhYXs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3CMeO Hf CHj HcQ Hf OGhhO GdMeOi GdMfHdi GdeTghQ HGHf GdHdGZi s)
(3ChdgG (B:s
(3CeG HYO aEf LeGYI ef GUMGHi GMHhG GdJTGZd HYde GdhYXaQZH CUMGHi ai EedGA cJGH jYfi Yf GdfXQ ai Jdc GdcJH aCLHJge aCedjJ ai gPG GdcJGH eG HI eLdS s
(3BNQgG (B:s
(3jfJgi HBNQ GdeLdS GdKGfi ai PcQ GdWgGQI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bhHdJ Ydi GdCUd Gdefbhdg efg s
(3GdejcQhajde Hg Jda s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
Keywords: (3GdJUha hGdBOGH GdTQYjIs